Physicochemical, biological and organoleptic indicators in banana silage (Musa sapientum) for pig feeding - Caicedo, W.; Vargas, J. C.; Uvidia, H.; Samaniego, E.; Valle, S.; Flores, L.; Moyano, J.; Aguiar, S. (Cuban Journal of Agricultural Science, 2017)
In order to evaluate the physicochemical, biological and organoleptic indicators in green banana silage (Musa sapientum)for use in pig feeding, four silages with waste banana were carried out. The treatments were: natural yogurt (NYGB), whey (WGB), whey and 5 % molasses B (WGBMB5) and whey and 10 % molasses B (WGBMB10). The experiment was conducted using a completely randomized single design. The means were contrasted with the Duncan test (P <0.05). The variables temperature, pH, fungi, yeasts, total coliforms, Escherichia coli, Clostridium spp., Salmonella spp., odor, color and consistency at 1, 4, 8, 15, 30 and 60 d were studied. With respect to temperature, on day one, the treatments NYGB and WGBMB5 showed the highest value (P < 0.05) (22.50 ºC; 22.51 ºC).On the day four, the silages NYGB and WGB had the highest value (P < 0.05) (22.49 ºC - 22.48 ºC). From day eight, to day 60, in the WGBMB10 the highest temperature was reached (22.83 - 22.53 ºC). Regarding pH, on day one, there were no differences (P> 0.05) between treatments: NYGB (4.39), WGB (4.33), WGBMB5 (4.36) and WGBMB10 (4.35). At day four, the pH was proportionally reduced in the silages, and was higher in treatment 1_NYGB, in 0.31 units. Then, the pH was stabilized in all silages. The NYGB treatment had the lowest value (P <0.05) (4.00 - 4.02). Fungi and yeasts were on day one, and then absent. During the study there were no total coliforms or Escherichia coli. Neither Clostridium spp. nor Salmonella spp. The silages showed odor (fermented sweet), color (yellowish coffee) and consistency (semi-hard). The physicochemical, microbiological and organoleptic indicators of silages, up to day 60, had a right performance, suitable for their use in pig feeding. Key words: food, pigs, green banana, fermentation, microorganisms.